The Transatlantic Blue Diplomacy - Ioana Gutu (CES Working Papers, 2016)
The international diplomatic environment has reached to an unprecedented development, involving one of the newly specialized diplomatic types, namely the economic diplomacy. At the core of the fast movements in the diplomatic spheres across the Globe are the international agreements like the Transatlantic Trade and Investment Partnership (TTIP) that determined diplomacy to dissolve into new subtypes, evolving from ground to the ocean and implementing new ways of achieving economic and climate sustainability. One of the newly created diplomatic spheres, is the blue ocean diplomacy that acts mainly in accordance with the rules and regulations that are being applied to the transatlantic economy. Even though TTIP encourages the increase of trade flows across the Atlantic, it will also ease the foreign investment procedures that, under the approach of keeping a sustainable environment, will represent one of the most important initiatives in implementing the blue economy concept within the framework of the transatlantic diplomacy.
Keywords: F02; 330; EU; US; economic diplomacy; blue economy